Thoracoscopic Vertebral Body Tethering for Adolescent Idiopathic Scoliosis: Follow-up Curve Behavior According to Sanders Skeletal Maturity Staging. Issue 22 (15th November 2020) - Alanay, Ahmet; Yucekul, Altug; Abul, Kadir; Ergene, Gokhan; Senay, Sahin; Ay, Binnaz; Cebeci, Barbaros Omer; Yalinay Dikmen, Pinar; Zulemyan, Tais; Yavuz, Yasemin; Yilgor, Caglar
Abstract : Study Design: Retrospective analysis of prospectively collected data. Objective: To report the follow-up curve behaviors in different Sanders staging groups. Summary of Background Data: Vertebral body tethering (VBT) is a growth modulation technique that allows gradual spontaneous follow-up curve correction as the patient grows. There is a lack of scientific evidence regarding appropriate patient selection and timing of implantation. Methods: Patients were grouped into five as: Sanders 1, 2, 3, 4–5, and 6–7. Data were collected preoperatively, at the day before discharge, and at each follow-up. Outcome measures were pulmonary and mechanical complications, readmission, and reoperation rates. Demographic, perioperative, clinical, radiographic, and complication data were compared using Fisher–Freeman–Halton exact tests for categorical variables and Kruskal-Wallis tests for the continuous variables. Results: Thirty-one (29 F, 2 M) consecutive patients with a minimum of 12 months of follow-up were included. The mean age at surgery was 12.1 (10–14). The mean follow-up was 27.1 (12–62) months. The mean preoperative main thoracic curve magnitude was 47° ± 7.6°. For all curves, preoperative and first erect curve magnitudes, bending flexibility, and operative correction percentages were similar between groups (for all comparisons, P > 0.05). The median height gained during follow-up was different between groups ( P < 0.001), which was reflected into median curve correction during follow-up. Total curve correction percentage was different between groups ( P = 0.009). Four (12.9%) patients had pulmonary and six (19.4%) had mechanical complications. One (3.2%) patient required readmission and two (6.5%) required reoperation. Occurrence of pulmonary complications was similar in Sanders groups ( P = 0.804), while mechanical complications and overcorrection was significantly higher in Sanders 2 patients ( P = 0.002 and P = 0.018). Conclusion: Follow-up curve behavior after VBT is different in patients having different Sanders stages. Sanders 2 patients experienced more overcorrection, thus timing and/or correction should be adjusted, since Sanders 3, 4, and 5 patients displayed a lesser risk of mechanical complications. Level of Evidence: 3. Abstract : Follow-up curve behaviors for patients in different Sanders groups who had similar curves that were corrected with a similar strategy were found to be different. This information forms a basis for clinical decision-making and surgical planning in which adolescents at various stages of maturity are attributed different risks and benefits.